Transformasi Digital Pengaruhnya Terhadap Kinerja Bank Digital - Henry Gunawan (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Digital banking transactions have increased by 158% in the last 5 years (2018-2022). There is a phenomenon of switching transactions from the original customer coming to the bank branch to now online through a mobile phone or laptop computer. This digital transformation has made many banks adjust to create their own applications that can be installed on mobile phones or computers or laptops to satisfy the desires of their customers. This digital transformation is important to be researched considering the increasingly rapid technological changes, such as stated in VUCA (volatility, uncertainty, complexity and ambiguity). This research also conveys the relationship between digital transformation and VUCA. This research was conducted using a qualitative method by referring to several references. The results of this research require digital transformation for banks in addition to creating a new digital ecosystem and making their banks survive in the market.